Ответы и объяснения

  • DayZ2
  • середнячок
2013-09-08T09:50:20+00:00
Выражение: a^2-a*x/a^2*x-a*x^2-1/x
Ответ: a^2-x^2/a-a*x^2-1/x
Решаем по действиям:1. a/a^2=a^(-1)  a/a^2=a^(1-2)  1.1. 1-2=-1      -2       _1_      -12. a^(-1)=1/a3. x*x=x^2  x*x=x^(1+1)  3.1. 1+1=2      +1       _1_       2
Решаем по шагам:1. a^2-a^(-1)*x*x-a*x^2-1/x  1.1. a/a^2=a^(-1)      a/a^2=a^(1-2)    1.1.1. 1-2=-1          -2           _1_          -12. a^2-x/a*x-a*x^2-1/x  2.1. a^(-1)=1/a3. a^2-x^2/a-a*x^2-1/x  3.1. x*x=x^2      x*x=x^(1+1)    3.1.1. 1+1=2          +1           _1_           2